Não sou régua para nivelar: Narrativas sobre processo de escolarização e racismos cotidianos de promotores/as negros/as - Cabral, Ingrid Marques (2022)
This research analyzes the schooling processes of self-declared black state prosecutors for the purpose of identifying singularities that may have contributed to the theis occupation on these disired positions and also analyze cases of racism experienced. Therefore, the methodology listed turned to the production of qualitative data from semi-structured life narrative interviews (BERTAUX, 2010) with 04 self-declared black prosecutors, 02 women and 02 men. operating in the Northeast, South and Southeast regions. In addition to the production of qualitative data, there was an analysis of scientific works that focus on the processes of schooling of black men and women in the field of law, as well as quantitative research, in order to carry out a comparative analysis.